EDUCATIONAL PACKAGE TO ADRESS INEFECTIVE BREASTFEEDING IN PRIMIPARAOUS MOTHER - Sriningsih, Iis -; Elisa, Elisa; Wagiyo, Wagiyo; Kuntari, Sri (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Breastfeeding is the best way for maternal health as well as healthy growth and development of the baby. However, not all postpartum mothers succeed in breastfeeding smoothly. Various problems are encountered by mothers after giving birth related to breastfeeding, such as delayed breast milk production, engorged nipples, flat nipples, and even issues where the baby finds it difficult to latch onto the mother's nipple. One of the solutions for breastfeeding issues is providing an educational package. Objective: The aim of the nursing analysis is to apply an educational package to effectively address breastfeeding problems in postpartum primiparous mothers.Method: The study employs a case study on three primiparous postpartum clients who are facing breastfeeding challenges. The nursing process approach is used along with evidence-based practice. Results: The nursing intervention was conducted through four visits with the three primiparous mothers facing breastfeeding problems. The results showed improvement in their breastfeeding status. However, there was one indicator that was not achieved, which is direct breastfeeding. The educational package includes health education, a pocket-sized booklet, direct guidance on correct breastfeeding and attachment techniques for mothers with flat nipple issues, counseling, oxytocin massage, and Hoffman exercises to address flat or inverted nipple problems. The study concludes that an educational package can be applied effectively to address breastfeeding problems in postpartum primiparous mothers.